Impact on Consumer Buying Behaviour of Tech Products Due to Influencers - Rajdeep Nath (International Journal of Advanced Science and Technology, 2020)
As technology is transforming rapidly, the way people purchase products is also changing. Earlier people used to visit bricks and mortar stores, feel the product and then purchase.  The development of social media which is a new concept of electronic marketing is developing quickly. This advancement has made consumers change their buying process. The consumer now understands the product and then the buying happens. They refer to influencer videos that are available online before buying a product. The method adopted by companies of using content creators also known as influencers for marketing has shown high potential in driving the sales of the product. In order to attain good competitive advantage companies are trying to maintain a strong media presence to drive sales. In light of this observation, this study aims to provide a better understanding of influencer techniques of marketing that are applied by tech companies and also to interpret the role of the influencers on the consumer buying behaviour in the tech industry.  Influencers play a vital role in the buying behaviour of a consumer while buying a tech product.Research Methodology - The theoretical analysis of the study will be conducted by collecting secondary data and the empirical study will be conducted by the quantitative survey method. The survey will comprise of consumer buying tech products of the age group 18 years to 30 years.